PROSES BRAIN GAIN PELAKU MUDA AGRIBISNIS DI DATARAN TINGGI JAWA BARAT - MAHRA ARARI HERYANTO, IWAN SETIAWAN, ADI NUGRAHA, (Jurnal Social Economic of Agriculture, 2018)
This study aimed to describe: (1) the background of the brain gain actors; (2) the shoreline of brain gain actors; (3) basic decisions of actors to do a brain gain; (4) motivation of actors to do a brain gain; (5) the brain gain actors adaptation process; and (6) the design model of the brain gain process in the highlands of West Java. The results showed that: (1) the average of brain gain actorshave undergraduate education, non-formal education, work experience in non-agriculture and business experiencein agriculture.They are categorized into primary actors, secondary actors and tertiary actors; (2) the shoreline actors spread of major cities in West Javato overseas; (3) the decision of brain gain is based on the consideration mental-rational, personal-emotional, awareness-collectivity, productive-adaptive, exploitative-reproductive, informal-integration, innovation-regeneration and participation-nonformal; (4) the brain gain motivation of primary actorsis guarantee income of vegetables on-farm, secondary actors is guarantee incomeof vegetable off-farm and tertiary actors isenvrinment advocating and creation of alternativebusiness; (5) the adaptation process of actors ranging from 1-3 years, through four stages of evolution and adaptation types are varied; and (6) the process of brain gain a precondition in independence developmentof young actors. The adaptation process of brain gain acors is slow, hence the need to strengthen the agribusness practical experience to potential brain gain actorswill return to the rural area.Keywords : agribusiness young actor, shoreline, decision, motivation, adaptation, brain gain